Blood Glucose Levels in Type II Diabetes Mellitus Patients Who Consumed Carbohydrates and Cholesterol: A Cross-Sectional Study in The Outpatient Setting - Lisdayanti, Lisdayanti; Basri, Moh.; Dwiyana, Asnurbaety; Nurdin, Andi Asmiati; Saleh, Rahmat (Jambura Medical and Health Science Journal, 2025)
Introduction: Diabetes mellitus is a disease caused by disorders related to the insulin hormone. This study aims to determine the results of fasting blood glucose levels in Type II Diabetes Mellitus sufferers who consume carbohydrates and cholesterol in the outpatient Universitas Indonesia Timur Wisata Hospital, Makassar City.Methods: The type of research used is observational with a cross-sectional approach. The sample was 10 outpatients with type II diabetes mellitus at the Wisata Hospital of the Universitas Indonesia Timur. Data were collected using purposive sampling. The research results are made in tabular form and narrated.Results: The average fasting blood glucose (FBG) level is 129.3 mg/dl, which was included in the diabetes category. The average 2-hour post-prandial blood glucose level (BG2PP) value was 244.1 mg/dl, which was also included in the diabetes category. Carbohydrate and cholesterol consumption had an average value of 255.6 grams and 223.9 mg, respectively.Conclusion: The average fasting blood glucose and 2-hour post-prandial blood glucose values are included in the diabetes category. Impaired FBG increases the patient's risk of developing diabetes in the future compared to if the patient has impaired blood glucose tolerance.Keywords: Blood glucose levels, carbohydrate intake, cholesterol intake